2015
DOI: 10.1080/09507116.2014.932985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of proportion of phases in joints welded from duplex stainless steel pipes by means of non-destructive testing

Abstract: Duplex stainless steels (DSSs) combine excellent corrosion resistance and high mechanical strength, due to the fine twophase microstructure composed of similar amounts of ferrite (d) and austenite (g). These alloys are used in piping and industrial equipment for which a high strength-to-weight ratio is required, especially in building construction and off-shore assembly. However, welding operating conditions can promote a significant microstructural imbalance of these phases, resulting in a decrease of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…However, the nature and types of welded joints produced from these welding techniques when trying to achieve the lightweight product concept are not free from their problems. It has been suggested that welding techniques are critical to the management of manufacturing energy consumption, the cost of achieving the lightweight product concept, and the quality and reliability of the welds produced [6]. Hence, it has been recommended that welded joints under the lightweight product concepts should be monitored continuously, such as to ensure balance and stability in the micro-structural and mechanical properties of the welded joints [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature and types of welded joints produced from these welding techniques when trying to achieve the lightweight product concept are not free from their problems. It has been suggested that welding techniques are critical to the management of manufacturing energy consumption, the cost of achieving the lightweight product concept, and the quality and reliability of the welds produced [6]. Hence, it has been recommended that welded joints under the lightweight product concepts should be monitored continuously, such as to ensure balance and stability in the micro-structural and mechanical properties of the welded joints [7].…”
Section: Introductionmentioning
confidence: 99%